2021
DOI: 10.1101/2021.09.21.461299
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chicken Auditory Supporting Cells Express Interferon Response Genes during Regeneration towards Nascent Sensory Hair CellsIn Vivo

Abstract: The avian hearing organ is the basilar papilla that, in sharp contrast to the mammalian cochlea, can regenerate sensory hair cells and thereby recover from complete deafness within weeks. The mechanisms that trigger, sustain, and terminate the regenerative response in vivo are largely unknown. Here, we profile the changes in gene expression in the chicken basilar papilla after aminoglycoside antibiotic-induced hair cell loss using RNA-sequencing. The most prominent changes in gene expression were linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 142 publications
(237 reference statements)
0
1
0
Order By: Relevance
“…Prior evidence has demonstrated that both IGFBP3 and IGFBP5 play key roles in supporting the development of the cochlea during mammalian development ( 39 ). We also found that NREP expression (neuronal regeneration-related protein), which was recently shown to be expressed by regenerating chicken hair cells ( 40 ), was reduced throughout HCMV infection ( Table S1 ). Others have demonstrated that SOX11 is both necessary and sufficient for the development of hair cells in the inner ear ( 41 ), and the data suggest that HCMV infection reduced SOX11 expression at both timepoints ( Table S1 ).…”
Section: Resultsmentioning
confidence: 58%
“…Prior evidence has demonstrated that both IGFBP3 and IGFBP5 play key roles in supporting the development of the cochlea during mammalian development ( 39 ). We also found that NREP expression (neuronal regeneration-related protein), which was recently shown to be expressed by regenerating chicken hair cells ( 40 ), was reduced throughout HCMV infection ( Table S1 ). Others have demonstrated that SOX11 is both necessary and sufficient for the development of hair cells in the inner ear ( 41 ), and the data suggest that HCMV infection reduced SOX11 expression at both timepoints ( Table S1 ).…”
Section: Resultsmentioning
confidence: 58%